2008
DOI: 10.1590/s0034-89102008000200008
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerabilidade ao HIV/Aids de pessoas heterossexuais casadas ou em união estável

Abstract: OBJECTIVE:To study knowledge, preventive behavior, and perception regarding HIV/AIDS of heterosexual men and women that are married or in a common-law marriage. METHODS:Exploratory study carried out in the Federal District of Brazil, between 2001 and 2002. Heterosexual men and women (N=200) aged 18 and 49, married or in a common-law marriage were divided into two groups: (I) 50 couples approached in public places, and (II) 100 users of a Basic Health Unit, 50 were women and 50 were men. The instrument for data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 2 publications
(6 reference statements)
0
3
0
5
Order By: Relevance
“…As regards condom use, in this study, it was observed that more than 40% of the women had unsafe sex, independently of whether they had a fixed or occasional partner, and of the partner's serological status. International ( 6 - 7 , 21 ) and Brazilian ( 20 , 22 ) studies revealed that gender-based power inequalities, as well as the standards of stable relationships, determine women's low power of negotiation with regard to safe sex. The expectation of motherhood is another factor that contributes to unsafe sexual practices ( 6 ) .…”
Section: Discussionmentioning
confidence: 99%
“…As regards condom use, in this study, it was observed that more than 40% of the women had unsafe sex, independently of whether they had a fixed or occasional partner, and of the partner's serological status. International ( 6 - 7 , 21 ) and Brazilian ( 20 , 22 ) studies revealed that gender-based power inequalities, as well as the standards of stable relationships, determine women's low power of negotiation with regard to safe sex. The expectation of motherhood is another factor that contributes to unsafe sexual practices ( 6 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Segundo Silva (2002), o uso da camisinha está relacionado às relações sexuais com pessoas "desconhecidas", fato que caracteriza a existência de um pensamento "mágico", que traz o entendimento de que a aparência e o pseudoconhecimento do perfil comportamental da outra pessoa possam garantir a proteção à AIDS. Por outro lado, Maia et al (2008) acrescentam que a relação histórica do uso do preservativo com a prostituição e as relações extraconjugais podem inibir a incorporação deste hábito no território do casamento. Malta et al (2006) constataram, em seu estudo, que quanto mais os caminhoneiros tinham intimidade com as parceiras sexuais, menos eles usavam o preservativo de forma consistente.…”
Section: Prevenção Da Aids: "é Melhor Usar Camisinha E Ser Fiel!"unclassified
“…In line with the development of more general literature on the relationship between gender and health in the field of HIV/AIDS studies, the centrality of gender issues regarding vulnerability to HIV, as well as for the prevention of AIDS and other sexually transmitted diseases (STDs), is recognized 5,6 . In general, it is understood that the recognition of the need and the decision to adopt preventive measures against HIV are influenced by the way that the relationships between men and women are configured socially and culturally, and by how masculinities and femininities are designed and affirmed within the affective and sexual relations [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%